(untitled) (Annual of the Faculty of Philosophy in Skopje, 2008)
This paper is animated from the existing denying the need of investigation and research the history in the past and nowadays. It discusses the theoretical polemics with the intellectual elite who sets the globalistic ideas over the national identity. Through the relation between the national identity and the historical legitimate the paper explains the need’, use and the abuse of the history as an instrument to introduce particular political goals of groups, organizations, state and overstate structures.